PolySialic Acid Nanoparticles Actuate Complement-Factor-H-Mediated Inhibition of the Alternative Complement Pathway: A Safer Potential Therapy for Age-Related Macular Degeneration - Sheri L. Peterson; Anitha Krishnan; Diyan Patel; Ali Khanehzar; Amit Lad; Jutamas Shaughnessy; Sanjay Ram; David Callanan; Derek Kunimoto; Mohamed A. Genead; Michael J. Tolentino (MDPI AG, 2024)
The alternative pathway of the complement system is implicated in the etiology of age-related macular degeneration (AMD). Complement depletion with pegcetacoplan and avacincaptad pegol are FDA-approved treatments for geographic atrophy in AMD that, while effective, have clinically observed risks of choroidal neovascular (CNV) conversion, optic neuritis, and retinal vasculitis, leaving room for other equally efficacious but safer therapeutics, including Poly Sialic acid (PSA) nanoparticle (PolySia-NP)-actuated complement factor H (CFH) alternative pathway inhibition. Our previous paper demonstrated that PolySia-NP inhibits pro-inflammatory polarization and cytokine release. Here, we extend these findings by investigating the therapeutic potential of PolySia-NP to attenuate the alternative complement pathway. First, we show that PolySia-NP binds CFH and enhances affinity to C3b. Next, we demonstrate that PolySia-NP treatment of human serum suppresses alternative pathway hemolytic activity and C3b deposition. Further, we show that treating human macrophages with PolySia-NP is non-toxic and reduces markers of complement activity. Finally, we describe PolySia-NP-treatment-induced decreases in neovascularization and inflammatory response in a laser-induced CNV mouse model of neovascular AMD. In conclusion, PolySia-NP suppresses alternative pathway complement activity in human serum, human macrophage, and mouse CNV without increasing neovascularization.